Do maximal roller skiing speed and double poling performance predict youth cross-country skiing performance? - Stöggl, R.; Müller, E.; Stöggl, T. (Journal of Sports Science & Medicine, 2017)
The aims of the current study were to analyze whether specific roller skiing tests and cycle length are determinants of youth cross-country (XC) skiing performance, and to evaluate sex specific differences by applying non-invasive diagnostics. Forty-nine young XC skiers (33 boys; 13.8 ± 0.6 yrs and 16 girls; 13.4 ± 0.9 yrs) performed roller skiing tests consisting of both shorter (50 m) and longer durations (575 m). Test results were correlated with on snow XC skiing performance (PXC) based on 3 skating and 3 classical distance competitions (3 to 6 km). The main findings of the current study were: 1) Anthropometrics and maturity status were related to boys`, but not to girls` PXC; 2) Significant moderate to acceptable correlations between girls` and boys` short duration maximal roller skiing speed (double poling, V2 skating, leg skating) and PXC were found; 3) Boys` PXC was best predicted by double poling test performance on flat and uphill, while girls` performance was mainly predicted by uphill double poling test performance; 4) When controlling for maturity offset, boys` PXC was still highly associated with the roller skiing tests. The use of simple non-invasive roller skiing tests for determination of PXC represents practicable support for ski clubs, schools or skiing federations in the guidance and evaluation of young talent.